Dampak Hukum Mendirikan Bangunan Tanpa Izin Diatas Tanah Hak Milik Orang - St. Saradillah R. Ancong (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to determine and analyze the Impact and Legal Sanctions of Building Without Permission on Land Owned by Others and Legal Efforts If the Building is Built on Other People's Land. This study is a normative study using a legislative approach. From these problems, it is concluded that building without permission on other people's land is an act of land grabbing that violates the law. This action can be subject to criminal and civil sanctions, administrative sanctions. Legal efforts that can be taken are to submit an application to the regional authorities to vacate the land owned by the owner.